Pengaruh Penerapan Sistem Informasi Akuntansi, dan Pemahaman Akuntansi Berbasis Sak-Etap terhadap Kualitas Laporan Keuangan - Median Wilestari; Dita Safitri (AKRUAL : Jurnal Akuntansi dan Keuangan, 2021)
This study aims to determine the effect of implementing accounting information systems, and understanding accounting based on SAK-ETAP on the quality of financial reports in the study of savings and loan cooperatives in South Bekasi. The sampling technique in this study was purposive sampling. The sample used in this study were employees of savings and loan cooperatives in 17 cooperatives in South Bekasi with a total of 51 respondents. The data obtained were analyzed using the PLS (Partial Least Square) analysis technique through the SmartPLS 0.3 software. The results of the study show: (1) The application of accounting information systems has a positive and significant effect on the quality of financial reports, (2) the understanding of accounting based on SAK-ETAP has a positive and significant effect on the quality of financial reports.